The phosphatidylinositol 3-Kinase–AKT pathway in human cancer - Vivanco, Igor; Sawyers, Charles L. (Nature reviews. Cancer, 2002)
Key Points The phosphatidylinositol 3-kinase (PI3K) pathway regulates various cellular processes, such as proliferation, growth, apoptosis and cytoskeletal rearrangement. PI3Ks are heterodimeric lipid kinases that are composed of a regulatory and catalytic subunit that are encoded by different genes. The genes that encode the regulatory domains are also subject to differential splicing. Class IA PI3Ks are activated by receptor tyrosine kinases, and deregulation of their function has been implicated in several human cancers. One of the main functions of PI3K is to synthesize the second messenger PtdIns(3,4,5)P3 (PIP 3 ) from PtdIns(4,5)P 2 (PIP 2 ). AKT — a serine/threonine kinase that has a wide range of substrates — is activated by recruitment to the plasma membrane through direct contact of its pleckstrin-homology (PH) domain with PIP 3 , and phosphorylation at Thr308 and Ser473. Thr308 is phosphorylated by the 3-phosphoinositide-dependent protein kinase PDK1, whereas Ser473 is phosphorylated by a molecularly unidentified kinase, often termed PDK2. AKT acts downstream of PI3K to regulate many biological processes, such as proliferation, apoptosis and growth, but other signalling pathways are also known to be regulated by PI3K activity and might be involved in PI3K-mediated tumorigenesis. The available clinical evidence of PI3K-pathway deregulation in various cancers and the identification of downstream kinases that are involved in mediating the effects of PI3K (AKT, mTOR, PDK1 and ILK) provide potential targets for the development of small-molecule therapies. The importance of lipid–protein interaction domains (such as the PH domains of AKT and PDK1) for the activation of PI3K targets provides another potential strategy for developing targeted therapies. One signal that is overactivated in a wide range of tumour types is the production of a phospholipid, phosphatidylinositol (3,4,5) trisphosphate, by phosphatidylinositol 3-kinase (PI3K). This lipid and the protein kinase that is activated by it — AKT — trigger a cascade of responses, from cell growth and proliferation to survival and motility, that drive tumour progression. Small-molecule therapeutics that block PI3K signalling might deal a severe blow to cancer cells by blocking many aspects of the tumour-cell phenotype.